Health and the savings of insured versus uninsured, working-age households in the U.S. - Maude Toussaint-Comeau; Jonathan Hartley (Federal Reserve Bank of Chicago, 2009)
This paper examines the effect of a decline in health on the savings and portfolio choice of young, working individuals and the differences between insured and uninsured cohorts using the 2001 Survey of Income and Program Participation. We find that insured individuals are significantly likely to divest from risky asset holdings in response to a decline in health, controlling for variables such as income, age, and out-of-pocket medical expenses. Unlike many previous papers, which dismiss health and portfolio choice associations among retired individuals on the basis of unobserved heterogeneity, we find that our results for working individuals are robust when using fixed effects models in a three-year longitudinal panel. Consistent with an overall theory of risk, we find that the relationship between an onset of poor health and an increased aversion to risky assets among the insured is strongest (only apparent) among married-couple households.
Keywords: G11; I11; I12; J22; D1; 330; Health Insurance; Portfolio Choice; Health Conditions; Risk Hedging; Household Behavior; Labor Supply